Nicaragua Poverty Assessment : Challenges and Opportunities for Poverty Reduction, Volume 2. Annexes - World Bank (Washington, DC, 2013)
The purpose of this Poverty Assessment is to provide background material and analysis that will assist the Government in designing this strategy, but it is not itself designed to formulate the strategy. Chapter 1 looks at the macro situation in historical perspective, including structural reform during the 1990s, and the current debt and balance of payments situation. Chapter 2 examines poverty in Nicaragua today and during 1993-98 and includes the results of a qualitative assessment of poverty. Chapter 3 looks at public expenditures in the social sectors and their impact on poverty. Chapter 4 looks at rural poverty and agriculture, while Chapter 5 lays out key issues that would be important to address in a poverty reduction strategy. Some key priorities emerge from the analysis that should be considered: 1) Broad-based growth is essential to reduce poverty. 2) Poverty reduction is limited by population growth. 3) Sustaining rural income growth. 4) Improvements are needed in the public sector to build strong programs that reach the poor. 5) Foreign capital inflows distort expenditures. 6) Donors share the responsibility with the Government to reconsider priorities in order to ensure greater impact of development assistance on poverty reduction. 7) Sustaining the provision of basic social services and building human capital. 8) Establishing effective social protection mechanisms for the poor.